Determination of Temperature-Dependent Stress State in Thin AlGaN Layer of AlGaN/GaN HEMT Heterostructures by Near-Resonant Raman Scattering - Yanli Liu; Xifeng Yang; Dunjun Chen; Hai Lu; Rong Zhang; Youdou Zheng (Advances in Condensed Matter Physics)
The temperature-dependent stress state in the AlGaN barrier layer of AlGaN/GaN heterostructure grown on sapphire substrate was investigated by ultraviolet (UV) near-resonant Raman scattering. Strong scattering peak resulting from the A1(LO) phonon mode of AlGaN is observed under near-resonance condition, which allows for the accurate measurement of Raman shifts with temperature. The temperature-dependent stress in the AlGaN layer determined by the resonance Raman spectra is consistent with the theoretical calculation result, taking lattice mismatch and thermal mismatch into account together. This good agreement indicates that the UV near-resonant Raman scattering can be a direct and effective method to characterize the stress state in thin AlGaN barrier layer of AlGaN/GaN HEMT heterostructures.